1996
DOI: 10.1073/pnas.93.3.1038
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neuroblastoma is a peripheral primitive neuroectodermal tumor related to Ewing sarcoma.

Abstract: Olfactory neuroblastoma (ONB) is a malignant tumor of the nasal mucosa whose histogenesis is unclear. A relationship to neuroblastoma (NB), a pediatric tumor of the sympathetic nervous system, is based on morphologic similarities and the expression of similar neural antigens. However, the clinical presentation of ONB differs from that of NB, and MYCN amplification characteristic of NB is not observed. We have therefore examined the relationship of this malignancy to other classes of neural tumors. appear to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 35 publications
2
46
0
2
Order By: Relevance
“…In ENB the t(11;22)(q24;q12) has been detected in two out three metastatic cell lines (Whang-Peng et al, 1987;Cavazzana et al, 1988) and the presence of trisomy 8, a second non-random chromosomal aberration in pPNET-ETs, has been found in one of three short-term cultures of primary ENB (VanDevanter et al, 1991). The cytogenetic results were further confirmed by the molecular analysis carried out by reverse transcription polymerase chain reaction (RT-PCR) on six primary ENBs (Sorensen et al, 1996). In four of them (two of which originated in the previously cited cell lines) (Cavazzana et al, 1988), the presence of EWS/FLI-1 fusion transcript (Sorensen et al, 1994) was identified.…”
supporting
confidence: 52%
“…In ENB the t(11;22)(q24;q12) has been detected in two out three metastatic cell lines (Whang-Peng et al, 1987;Cavazzana et al, 1988) and the presence of trisomy 8, a second non-random chromosomal aberration in pPNET-ETs, has been found in one of three short-term cultures of primary ENB (VanDevanter et al, 1991). The cytogenetic results were further confirmed by the molecular analysis carried out by reverse transcription polymerase chain reaction (RT-PCR) on six primary ENBs (Sorensen et al, 1996). In four of them (two of which originated in the previously cited cell lines) (Cavazzana et al, 1988), the presence of EWS/FLI-1 fusion transcript (Sorensen et al, 1994) was identified.…”
supporting
confidence: 52%
“…Most ONBs do not exhibit balanced translocations and the presence of fusion genes in patient samples and cell lines [49, 50]. Early research improperly suggested ONB exhibiting a translocation (11;22)(q24;q12) and producing an EWS/FLI1 transcript, which might cause misclassification to primitive neuroectodermal tumors (PNETs) [51, 52]. …”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…With the widespread emergence of molecular diagnostic techniques applicable to paraffinembedded tissue, it was initially suggested that ONB was a form of peripheral neuroectodermal tumor (PNET), based on the apparent finding of the t(11;22)(q24;q12) translocation characteristic of Ewing's sarcoma and PNET in some ONB (95). However, a more recent study performing RT-PCR on 11 ONBs failed to find the chimeric EWS/FLI1 transcript in any of these tumors (96).…”
Section: Olfactory Neuroblastomamentioning
confidence: 99%